Spatial distribution of thermally induced residual stresses in HF-CVD diamond coatings on microstructured steel surfaces - Göltz, Maximilian; Helmreich, Thomas; Börner, Richard; Kupfer, Tobias; Schubert, Andreas; Rosiwal, Stefan (Diamond and Related Materials, 2023)
The chemical vapour deposition (CVD) of mechanically stable diamond layers on steel remains a big challenge that is difficult to solve. As a prerequisite to prevent the undesired graphite formation during the diamond CVD process, we apply a 5 μm thick CVD titanium-nitride interlayer with boron doping (TiNB). However, the adhesion of the diamond layer is still limited due to the large mismatch of thermal expansion between diamond and steel, that causes very high residual stresses in the diamond coating during cooling. This paper shows two approaches to reduce these stresses and produce well-adherent, thick diamond layers on a hardened steel substrate: First, by deterministic surface structuring and modelling of the surface microstructure, to achieve a distribution of said residual stresses. Second, by exploiting the volume expansion during the austenite to ferrite transformation, to minimise the difference in thermal expansion. Using X46Cr13 steel (1.4034), the stochastic surfaces of the state-of-the-art particle blasting pretreatment have been analysed to replicate a most similar but deterministic surface microstructure by a newly developed “ultrasonic vibration superimposed machining” (UVSM) process. Well adherent polycrystalline diamond coatings (1 μm–16 μm) have been deposited on steel substrates with the TiNB interlayer and a sufficient cooling treatment at the end of the CVD diamond process. The quenching generates a significant decrease of the overall expansion coefficient of the steel by the martensite/bainite formation (transformation of austenite to ferrite and iron carbide) at around 380 °C. Dilatometer measurements prove that the austenitic steel substrate at this temperature is equal in length to the ferritic steel at room temperature. The surface morphology and layer system were analysed by light and electron microscopy, the residual stresses in the diamond layer were quantified by Raman spectroscopy. Micro-Raman mappings show the spatial distribution of stresses at a resolution of 5 μm with slight tensile stresses at the topographical maxima (“peak”) of the machined structure and high compression stresses in the topographical minima (“valley”) in a range from +1.5 GPa to −9 GPa. These stress-maps reveal that the levels and ranges of residual stresses are strongly influenced by the surface structure of the underlying substrate and can be correlated to the ratio of coating thickness over roughness.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Cooling stress; Diamond on steel; Micro-Raman mapping; Substrate microstructure; Surface morphology; Thermal expansion of steel; Ultrasonic vibration superimposed machining (UVSM)